EFFECT OF PURIFICATORY MEASURES THROUGH COW’S URINE AND MILK ON STRYCHNINE AND BRUCINE CONTENT OF KUPEELU (STRYCHNOS NUXVOMICA LINN.) SEEDS - Mitra, Swarnendu; Shukla, V J; Acharya, Rabinarayan (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Strychnos nux vomica Linn.(Loganaceae) commonly known as Nux vomica (Kupeelu), is a poisonous plant and its seeds are used widely in Ayurvedic system of medicine since time immemorial. Ayurveda advocates that nux vomica seeds are to be administered in therapeutics only after going through certain purificatory measures (Shodhana). There are more than six media: cow’s urine (Go mutra), cow’s milk (Go dugdha), cow’s ghee (Go ghrita), Kanji (thin gruel), castor oil (Eranda taila) and fresh ginger juice (Ardraka swarasa) etc., which have been reported in different classical texts of Ayurveda for proper processing of nux vomica seeds. In this study, an attempt has been made to purify the seeds by using three different methods as described in ancient treatise by using cow’s urine and cow’s milk as media alone and together. This study revealed that all the methods studied reduced the toxicity of strychnine and brucine contents in comparison to the raw seeds as determined by HPTLC. Out of these three methods maximum reduction in strychnine and brucine contents was found when the seeds were purified by keeping them in cow’s urine for seven days followed by boiling in cow’s milk for three hrs.